2019
DOI: 10.1002/jcb.28662
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TINCR participates in ALA‐PDT‐induced apoptosis and autophagy in cutaneous squamous cell carcinoma

Abstract: This study aims to investigate whether terminal differentiation-induced ncRNA (TINCR) has an effect on apoptosis and autophagy induced by ALA-PDT in cutaneous squamous cell carcinoma (CSCC). A431 cells were treated with 5-aminolevulinic acid (ALA) solution at different concentrations and for different duration time. A431 cell viability was detected by Cell Counting Kit-8 (CCK-8) assay, relative TINCR messenger RNA expression was detected by quantitative reverse-transcription polymerase chain reaction (qRT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In this regard, the downregulation of TINCR in cSCC specimens could be correlated to the decrease in differentiation [ 116 ]. Additionally, some suggested that TINCR is involved in A431 cell apoptosis and autophagy induced by the combined treatment with 5-aminolevulinic acid and photodynamic therapy, via the ERK1/2-SP3 pathway [ 117 ]. Another lncRNA whose expression is lowered in cSCC is LINC00520, a new type that has only been reported in a few tumors.…”
Section: Non-coding Rna Modifications In Cutaneous Sccmentioning
confidence: 99%
“…In this regard, the downregulation of TINCR in cSCC specimens could be correlated to the decrease in differentiation [ 116 ]. Additionally, some suggested that TINCR is involved in A431 cell apoptosis and autophagy induced by the combined treatment with 5-aminolevulinic acid and photodynamic therapy, via the ERK1/2-SP3 pathway [ 117 ]. Another lncRNA whose expression is lowered in cSCC is LINC00520, a new type that has only been reported in a few tumors.…”
Section: Non-coding Rna Modifications In Cutaneous Sccmentioning
confidence: 99%
“…Others reported that the overexpression of TINCR suppressed cell proliferation and invasion in lung cancer cells, tongue squamous cell carcinoma, and cutaneous squamous cell carcinoma. And about the role of TINCR in the migration of rMSCs [12][13][14], in this study, we first used real-time quantitative RT-PCR to validate whether miR-761 regulates the expression of TINCR. Then, we evaluated the effect of Figure 4: Wnt2 is a potential target of miRNA-761.…”
Section: Discussionmentioning
confidence: 99%
“…TINCR, a terminal differentiation-induced lncRNA with 3.7 kb transcript, is discovered from human welldifferentiated somatic tissues [10]. There is growing evidence that TINCR is involved in various cellular processes, such as proliferation, apoptosis, autophagy, migration, invasion, and metastasis [11][12][13][14]. For instance, Xu et al found that the overexpression of TINCR regulates cell proliferation and apoptosis by affecting KLF2 mRNA stability in gastric cancer (GC) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggested that TINCR is involved in ALA-PDT-induced (5-aminolevulinic acid-photodynamic therapy-induced) apoptosis and autophagy in A431 cells. ALA-PDT promoted the expression of TINCR in A431 cells, and then TINCR promoted ALA-PDT-induced apoptosis and autophagy via the ERK1/2-SP3 (specificity protein 3) pathway (30).…”
Section: Tincrmentioning
confidence: 94%